Exhibition Managerial Training on Art Market Exhibition at Heritage Rest Area at KM 260 Banjara - Rahman, Athian, Muhammad; Lestari, Wahyu; Soesanto, Soesanto (Arty: Jurnal Seni Rupa, 2023)
The fine art market in Indonesia is experiencing a positive development, although it is still relatively small compared to developed countries. This increase is supported by the growing number of art exhibitions, art galleries, and museums in Indonesia, as well as the high public interest in fine art. Technology and social media have also played an important role in introducing Indonesian art to the international world, opening up more opportunities for Indonesian artists to be recognized more widely. However, there are a number of challenges faced in the development of the art market in Indonesia. One of the challenges is the lack of support from the government in developing art infrastructure. In addition, there is still a lack of public awareness of the importance of art and there are still many copyright violations in the art industry. The utilization of public spaces can create unique opportunities for artists to reach a wider audience, engage with communities more closely, and promote creativity and cultural diversity in public spaces. This exhibition managerial training activity uses participatory methods, provision of adequate resources, and appropriate utilization of information and communication technology. The aim is to strengthen community participation, improve access to and utilization of available resources, and have a significant and sustainable impact on the communities served. The training has improved artists' understanding of how to maximize art displays, and some booths have seen an increase in sales. This article notes that the training has positive potential on the art market manager, artists, and the community that participated in the training, as well as enriching the repertoire of fine arts in the area.